Epigenetic Modifications in the Retinal Pigment Epithelium of the Eye During RPE-Related Regeneration or Retinal Diseases in Vertebrates - Eleonora Grigoryan; Yuliya Markitantova (Biomedicines)
The retinal pigment epithelium (RPE) is a cellular source of retinal regeneration in lower vertebrates and a cellular source of retinal diseases in mammals, including humans. Both processes are based on a genetic program for the conversion of RPE cells into cells of other phenotypes: neural in the first case and mesenchymal in the second. RPE reprogramming in the neural direction is realized in tailed amphibians and bird embryos in vivo, but in higher vertebrates and humans, this process is realized in vitro. Epigenetic regulation determines the phenotypic plasticity of RPE cells, i.e., their choice of the cell differentiation pathway in animals of different classes. It has been suggested that the implementation of the genetic program for RPE reprogramming into different types of retinal neurons in adult amphibians and birds at the early stages of embryogenesis is conditioned by the specificity of the epigenetic landscape. The retinal RPE-dependent pathologies in mammals are characterized by different epigenetic signatures, and have a shared characteristic: specifically, a deficient epigenetic landscape (dysregulations in DNA methylation and histone modifications). Knowledge of the patterns and features of the epigenetic regulation of RPE cell behavior will allow us to obtain RPE cells that are in demand in medicine, from direct reprogramming with the possibility of epigenetically maintaining the cellular identities to the creation of neuro-regenerative technologies for the replacement therapy of RPE-dependent retinal pathologies in humans.